Determinants of consumers' purchase intention on digital business model platform: Evidence from Ethiopia using partial least square structural equation model (PLS-SEM) technique - Mulatu Tilahun; Eshetie Berhan Atanaw; Gezahegn Tesfaye (Journal of Innovation and Entrepreneurship, 2023)
Online digital market platform business model designers, marketers, and retailers can further expand their marketing strategies to draw in and keep customers to gain a competitive edge globally if they are aware of the elements influencing consumers' purchasing intentions. The purpose of this research is to identify the crucial variables impacting Addis Ababa University, Graduating Engineering Students' desire to purchase on online digital market platforms, and narrow the research gap on determinants of online purchase intention of Ethiopian consumers. This study adopted a descriptive and inferential survey design, epistemology assumption, and employed the positivism research philosophy approach to test the research hypotheses. The primary study technique used to collect relevant data was a closed-ended 5-point Likert scale questionnaire. The information was gathered from 100 Ethiopian, Addis Ababa University, graduating engineering students. With the use of SPSS version 23 and SmartPLS version 3.0 software, the data were examined using descriptive statistics and the inferential partial least square structural equation modeling (PLS-SEM) technique. The results of this study highlighted five useful decision-making elements that have an impact on the selected consumers' intention to buy on online digital market platforms including Website Design, Perceived Usefulness, Perceived Ease of Use, Trust, and Subjective Norms. The Practical Implication of this research is that with a clear understanding of the key determinants of consumers' purchase intention on online digital market platforms; manufacturers, online marketers, and retailers can create effective market strategies, enhance technology, and make smart marketing choices that will help them gain global competitive advantage. This study is unique in that it uses a new conceptual research framework and the partial least square structural equation modeling (PLS-SEM) technique to analyze relationships between determinant variables and consumers' intention to purchase on online digital market platforms. The major finding of this research provides empirical evidence towards the key determinant variables of consumers' purchase intention on online digital market platforms. The small sample size is one of the limitations to generalize the finding of this research. Future studies should focus on enlarging the sample size and assessing more determinant variables to get a generalizable result.
Keywords: 650; Digital business model; Online digital market platform; Online purchase intention; PLS-SEM